Fermentation of grain mash obtained from activated water - Паньків, Наталія Олегівна; Паляниця, Любов Ярославівна; Косів, Руслана Богданівна; Березовська, Наталія Іванівна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper proposes using the electrochemically activated water (catholyte and anolyte) in producing alcohol from starch raw materials, namely spelt, which possesses various functional properties. Catholyte and anolyte with the pH values of 10.7-11.1 and 2.1-2.8 respectively, were used at the batching stage. For the control sample, tap water with pH 7.4-7.8 was used. Batches were prepared with different spelt and water ratios - 1: 3 and 1: 2.2. Conditions of hydro-enzymatic batch treatment were as follows: dilution was conducted at 86-89oC for 2.5 h, saccharification - at 55-60°C for 30 min. Dry alcohol yeast Saccharomyces cerevisiae were used as alcoholic fermentation activators. Mash fermentation was carried out at 33°C. As a result of the research, the expediency of batch preparation from spelt based on catholyte and anolyte was proved since solids content in the mash increases by 2.1-4.3%. Brew, obtained from this mash has good technical and chemical characteristics. The alcohol content in it increases by 3.7-11.4%, so does the alcohol yield.